MEMBACA FENOMENA KABAR BOHONG PILPRES 2019 DI INDONESIA BERDASARKAN KACA MATA HERBERT MARCUSE, JÜRGEN HABERMAS, DAN ZYGMUNT BAUMAN - Prasetyo, Yohanes Wahyu (JAP UNWIRA, 2020)
Abstract Hoaxes were rampant before, during and after the 2019 presidential election. According to Herbert Marcuse’s point of view, the hoax phenomenon is closely related to capitalism, hence prioritizing profit gaining and ignoring truth. Consequently, the people are seen as things and objects. Further, according to Jürgen Habermas, the hoax phenomenon takes place because of lack of communicative dialog and ethical responsibility where mass media are used as weaponry means by political parties to make public opinions. In the meantime, Zygmunt Bauman is of the opinion that the hoax phenomenon demonstrates that the people are treated as outsiders, foreigners and the out-group